Lichen planus drugs re-purposing as potential anti COVID-19 therapeutics - Dr Shalini Gupta (Elsevier, 2023)
Aim or Purpose: The present study intends to investigate COVID-19 by targeting their main proteins with 17 selected drugs used for treating Oral Lichen Planus (OLP) which is a chronic muco-cutaneous disorder. Here, an attempt is made to gain better insight into the structure of various drugs targeting specific proteins which will be helpful in developing drugs useful for therapeutic and preventive measures. Materials and Methods: In silico studies, molecular docking and molecular dynamic simulations were performed to repurpose the therapeutic drugs (n = 17) which were used to treat OLP against COVID-19. In addition, the maximum binding affinities of the key protein spike glycoprotein, main-protease (Mpro) of coronavirus, and Angiotensin-Converting Enzyme-2 (ACE-2) in the human body were evaluated with the selected drugs. Results: Epigallocatechin-3-gallate (EGCG) showed the highest docking values among the drugs selected for repurposing. Among the target proteins, EGCG has shown maximum binding affinity with ACE-2 receptor. Further, according to the molecular dynamic simulation studies, EGCG has shown the least conformational fluctuations with Mpro. Conclusions: EGCG can be a potential inhibitor drug which can bind with ACE-2 receptor thus inhibiting the interaction of mainly Mpro protein and spike glycoprotein of SARS-CoV-2.Relevance for patients: EGCG, a natural compound shows antiviral potential having considerably high affinity and stability with SARS-CoV-2. It might be further employed as a lead drug against selective inhibitors of SARS-CoV-2 for the therapeutic management of COVID-19 patients after necessary clinical trials.